THE INFLUENCE OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON RETURN ON ASSETS IN CONSTRUCTION AND BUILDING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Baihaqi Ammy; Jasman Saripuddin Hasibuan (CERED Indonesia Institute, 2020)
This study aims to determine and analyze the effect of the Current Ratio on ReturAn On Assets, to determine and analyze the effect of Debt To Equity Ratio on Return On AsAsets and to determine and analyze the effect of Current Ratio and Debt To Equity Ratio on Return On Asset in Construction and Building Companies Listed on the Indonesia Stock Exchange. The approach used in this research is an associative approach. The population in this study were 18 construction and building companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling, obtained a total sample of 11 companies. The analysis technique used is multiple linear regression, classical assumption test, Hypothesis testing uses the t test to test the partial regression coefficient as well as the F test and determination coefficient of SPSS (Statistic Package the Social Science) software assistance in 2020. It is partially known that the Current Ratio has no significant effect on Return On Asset in Construction and Building Companies listed in Indonesia Stock Exchange (IDX). Partially it is known that the Debt to Equity Ratio has no significant effect on the Return On Assets of Construction and Building Companies listed on the Indonesia Stock Exchange (BEI). Simultaneously it is known that Current Ratio and Debt to Equity Ratio have no significant effect on Return On Assets in construction and building companies listed on the Indonesia Stock Exchange. Partially it is known that the Current Ratio has no significant effect on Return On Assets in construction and building companies listed on the Indonesia Stock Exchange (BEI). Partially it is known that the Debt to Equity Ratio has no significant effect on Return On Assets at Construction and Building Companies listed on the Indonesia Stock Exchange (BEI). Simultaneously it is known that Current Ratio and Debt to Equity Ratio have no significant effect on Return On Assets in construction and building companies listed on the Indonesia Stock Exchange. It is partially known that the Current Ratio has no significant effect on the Return On Assets of Construction and Building Companies listed on the Indonesia Stock Exchange (IDX). Partially it is known that the Debt to Equity Ratio has no significant effect on the Return On Assets of Construction and Building Companies listed on the Indonesia Stock Exchange (BEI). Simultaneously it is known that Current Ratio and Debt to Equity Ratio have no significant effect on Return On Assets in construction and building companies listed on the Indonesia Stock Exchange.